IMPROVING DIGITAL SKILL AND SOCIAL MEDIA NETWORKING IN BOBIN BUSINESS FOR MSME COMMUNITIES IN TANGGUNGAN TIMUR VILLAGE, SIDOARJO REGENCY - aditya Surya Nanda Aditya Surya Nanda; Fitryani Fitryani (SEAN Institute, 2022)
The purpose of this research is to find out how to improve the quality of human resources based on digital skills, to find out how to improve social media-based marketing on bobbin SMEs and how to encourage increased social media-based networking on bobbin SMEs. The benefits of developing bobbins can reduce craft waste that damages the environment. The research method uses qualitative by collecting data in the form of facts in the field. The results of the study show that digital skills are very helpful and provide benefits for MSME actors in the East Dependent Village, as evidenced by informants who previously used traditional methods in carrying out their business activities and were able to improve the quality of MSME actors in facing competition in the industrial era 4.0. Social media-based marketing is highly felt. the benefits of bobin SMEs by using social media such as Facebook and Instagram to introduce their products and increase the market. The increase in social media-based networking provides more potential to expand business networks and is able to form a community between suppliers and customers. so that networking becomes a component that Bobin SMEs feel the benefits